História e memória da luta do povo de Alagamar : experiências de vida e construção de práticas educativas em diálogo com a educação popular - Neves, Gildivan Francisco das (2014)
School isn t the only place for knowledge construction where individuals learn and teach. Social movements are, for example, spaces where educative practices can be set up. Based on this premise, this dissertation addresses the Struggle of the Alagamar people , a social movement that existed between 1975 and 1980, with focus on the educative practices of the Struggle of the Alagamar people . As the problem of the research, it establishes the following question: In what way do the educative practices set up within the Struggle of the Alagamar people dialogue with a perspective of Popular Education? The general objective of the study is to analyze, based on the experiences of the participating workers, the educative practices used by the Struggle of the Alagamar people . As specific objectives it aims to: understand how the construction of educative practices occurs within social movements; contextualize the Struggle of the Alagamar people in order to give a new meaning to the memory of the studied social movement; and, analyze how the resistance actions developed by the rural workers within the referred social movement were constituted in a space of construction of educative practices in the perspective of Popular Education. This research is based on theories from Social History, a theoretical field that proposes to work with history and memory of individuals who were not contemplated by the traditional historiography. Within this theoretic current, we adopt the concept of experience from Thompson (1987,1998), the concept of memory from Bosi (1994), Halbwachs (2006), Le Goff (2012) and Nora (1993), Popular Education from Carrillo (2007) and Freire (1967, 2011), among others, and, social movements from Batista (2007) and Kauchakje (2007). Methodologically, it s a research with a qualitative approach in the perspective of Oral History in its thematic modality. It works with the testimonials from two rural workers, one man and one woman, and a documental study in order to analyze the available documents: chap-books (folk literature), printed newspapers, the Archdiocesan Newsletter, nº.82 from January/February of 1980, the Fifth Pastoral Letter from Archbishop Dom José Maria Pires, and photographs. These sources permitted us to visualize aspects of the memory and history of the referred social movement, and the trajectories and experiences of the participants, which contributed to the analysis of our study object. We observed that the Struggle of the Alagamar people was constituted as a space of construction of educative practices where the rural workers, based on their experiences, in dialogue with external agents, educated themselves mutually in a perspective of Popular Education.